Analysis Of The Impact Of Economic Growth, Human Development Index (HDI) And Unemployment Rate On Poverty In Sumatra Island - Adrian Alamsyah; Armelly Armelly (Utan Kayu Publishing, 2024)
This study aims to analyze the impact of economic growth, the human development index, and the unemployment rate on poverty in each province on the island of Sumatra using panel data regression analysis with the Random Effect Model (REM) over the period 2013-2022. The results of the study indicate that each independent variable has a different effect on the dependent variable. The economic growth variable has a negative but not significant effect on the poverty level in each province on the island of Sumatra. Meanwhile, the human development index variable has a negative and significant effect, and the unemployment rate variable has a positive and significant effect on the poverty level in each province on the island of Sumatra for the period 2013-2022.